Recruiting and Retaining Party Activists - Pettitt, Robin T. author. aut Link
XIV, 97 p. 3 illus.
Keywords: ‘These interviews from the grassroots frontline of political party activism provide an important new perspective on how and why people become political activists. The insights are valuable both for political scientists and for those seeking to run political party organisations.’ –Mark Pack, Party President of the Liberal Democrats, author of Bad News and 101 Ways to Win an Election, editor of Liberal Democrat Newswire This book explores how experienced party organisers in the UK work to recruit and to retain party activists for local campaigning. Local door-to-door campaigning is widely regarded as being a key element in a successful election campaign. However, for door-to-door campaigning to work, a large number of volunteer activists are required. The question then is: How can parties identify, recruit and retain such volunteer activists? Based on interviews with highly experienced campaigners, original party documents, the wider campaigning and volunteering literature, numerous informal conversations and the author’s own experience of local campaigning over a 20 year period, this book provides an answer to that question. It shows how potential activists are identified, encouraged to become active and supported through their initial encounter with local campaigning. The author also shows how local parties can encourage activists to remain active by creating a ‘retention enhancing campaigning environment’ and what that involves. Robin T. Pettitt is Senior Lecturer in Comparative Politics at Kingston University, London, UK.